2015
DOI: 10.1111/avsc.12185
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting distribution patterns of invasive and naturalized non‐native species along environmental gradients in a semi‐arid montane ecosystem

Abstract: Questions Mountain systems have high abiotic heterogeneity over local spatial scales, offering natural experiments for examining plant species invasions. We ask whether functional groupings explain non‐native species spread into native vegetation and up elevation gradients. We examine whether non‐native species distribution patterns are related to environmental variables after controlling for elevation and, thus, driven by niche processes. Location The Wallowa Mountains, northeast Oregon, USA. Methods We surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…There is growing evidence in favour of the DEFH, but no study has yet concurrently explicitly tested both the DEFH and the ALH, nor have analyses of functional traits been used to complement nestedness analyses when assessing these hypotheses (but see Andersen et al. ). Therefore, the aim of this study was to investigate support for the DEFH and for the ALH along an elevational gradient using two complementary approaches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence in favour of the DEFH, but no study has yet concurrently explicitly tested both the DEFH and the ALH, nor have analyses of functional traits been used to complement nestedness analyses when assessing these hypotheses (but see Andersen et al. ). Therefore, the aim of this study was to investigate support for the DEFH and for the ALH along an elevational gradient using two complementary approaches.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, high-elevation sites with low species richness would comprise only widespread species, while lowland sites with high species richness would contain more range-restricted species (Wright & Reeves 1992). Several studies that looked at species richness and community structure of alien species along elevation gradients have, without implicitly testing for it, found that the DEFH plays a role in their studies (Py sek et al 2011;Pollnac et al 2012;Seipel et al 2012;Andersen et al 2015;Zhang et al 2015). The DEFH has also been identified as relevant at both small and large spatial scales (Seipel 2011;Dainese et al 2014;Pollnac & Rew 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X. strumarium was attacked naturally by Rust ( P. xanthii ) and E. struneuna infestations were identified from the leaves. The transect line was sixty meters long parallel to the road or riverside, this line was divided into three similar portions each of twenty meter long collected randomly and data were recorded using quadratic ring [96-98] ring (100×100 cm) according to standardized protocol [99]. Three whole cocklebur plants in each quadratic ring were selected randomly for measuring their growth parameters and other characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of natural enemy pressure was estimated with latitude. One-way analysis of variance conducted to test the effect of latitude on different growth parameters, natural enemy’s abundance and phyto-chemical yield extractions [99]. Principal component and redundant analysis were conducted to explore the multivariate relationship between natural enemy’s abundance and different abiotic trends.…”
Section: Methodsmentioning
confidence: 99%